Between Liberty and Faith: Exploring the Dynamics of Childfree Choices in the Islamic Perspective of Malaysia - Bin Samsudi, Syazwan; Busro, Busro (Tashwirul Afkar, 2023)
This study investigates the childfree lifestyle choice phenomenon in Malaysia, particularly within the framework of Islamic teachings as interpreted in "Tafsir Pedoman Muttaqin". Employing a qualitative approach, this research integrates qualitative analysis of religious texts and interviews with five Malaysian individuals. The study reveals that the decision to pursue a childfree life, influenced by factors such as individual freedom, economic considerations, and personal autonomy, contrasts with the interpretations of Islamic teachings on family and procreation. Key Islamic scriptures, notably QS Al-Baqarah: 187 and Al-Imran 14, underscore the significance of marital relations not solely for physical gratification but also for the purpose of producing righteous progeny. These findings illuminate a marked divergence between contemporary social trends and the traditional Islamic viewpoints on family and procreation in Malaysia. The study makes a significant contribution to academic discourse by presenting a unique perspective on how traditional Islamic interpretations shape attitudes toward contemporary lifestyle choices like childfree living. Additionally, it elucidates the intricate interplay of social, economic, and religious dynamics within Malaysian society. This research offers valuable insights that could inform policies and practices in reproductive health, education, and family counseling.